Concentration-Dependent Protection by Ethanol Extract of Propolis against γ-Ray-Induced Chromosome Damage in Human Blood Lymphocytes - Montoro, A. (Hindawi Publishing Corporation, 2011)
Radioprotection with natural products may be relevant to the mitigation of ionizing radiation-induced damage in mammalian systems; in this sense, propolis extracts have shown effects such as antioxidant, antitumoral, anti-inflammatory, and immunostimulant. We report for the first time a cytogenetic study to evaluate the radioprotective effect, in vitro, of propolis against radiation-induced chromosomal damage. Lymphocytes were cultured with increasing concentrations of ethanol extract of propolis (EEP), including 20, 40, 120, 250, 500, 750, 1000, and 2000 μg mL(−1) and then exposed to 2 Gy γ-rays. A significant and concentration-dependent decrease is observed in the frequency of chromosome aberrations in samples treated with EEP. The protection against the formation of dicentrics was concentration-dependent, with a maximum protection at 120 μg mL(−1) of EEP. The observed frequency of dicentrics is described as negative exponential function, indicating that the maximum protectible fraction of dicentrics is approximately 44%. Free radical scavenging and antioxidant activities are the mechanisms that these substances use to protect cells from ionizing radiation.